Initiation but no execution - modulation of peripheral blood lymphocyte apoptosis in rheumatoid arthritis - a potential role for heat shock protein 70 - Chuturgoon Anil A; Mody Girish M; Moodley Devapregasan (BMC, 2011)
Abstract Background Rheumatoid arthritis (RA) is a chronic autoimmune disease, which causes synovial damage. Persistence of lymphocyte infiltrates in the rheumatoid synovium has been attributed to abnormal apoptosis. While not comprehensively investigated, perturbations in peripheral blood lymphocyte (PBL) apoptosis may also be involved in perpetuation of autoimmune processes in RA. Methods We investigated total, CD4+ and CD19+ PBL apoptosis in our study cohort by monitoring the translocation of phosphatidylserine using the Annexin-V assay. To examine the role of death receptor mediated apoptosis as well as activation-induced-cell-death (AICD), PBLs were labeled with CD95/Fas and CD69 markers and enumerated by flow cytometry. Proteolytic activity of initiator and executioner caspases was determined by luminometry. DNA fragmentation assays were used to examine whether apoptotic signals were transduced to the nucleus. Quantitative PCR arrays were used to investigate apoptotic pathways associated with RA-PBLs. Since heat-shock-protein-70 (HSP70) is an inducible protein which modulates apoptotic signals, we determined HSP70 levels by intra-cellular flow cytometry and western blots. Results The RA-PBLs showed signs of elevated apoptosis whilst in circulation. These include increases in the loss of plasma membrane asymmetry, indicated by increased externalization of phosphatidylserine (especially in B-lymphocytes). RA-PBLs showed a bias to CD95/Fas mediated apoptotic pathways, but low levels of the CD69 marker suggested that this was not associated with immune activation. Although downstream markers of apoptosis such as caspase-3/7 activity, were increased, no DNA fragmentation was observed in RA-PBLs. Interestingly, elevated levels of apoptosis did not correlate with absolute lymphocyte counts in RA patients. Levels of HSP70 were highly elevated in RA-PBLs compared to controls. Conclusion The results suggest that while apoptosis may be initiated in RA-PBLs, they may lack commitment to fully executing the apoptotic program. This may be related to inhibition on apoptotic transduction by HSP70. This study provides evidence that abnormalities in RA-PBLs apoptosis may occur whilst still in circulation and may contribute to pathogenesis of the disease.